Job Satisfaction: The Role Of Organizational Culture As A Regression Variable On Employees At PPPPTK Boe Malang - Sa'adah, Ummi; Putra, Bryan Cadalora; Permatasari, Rr. Indah (Universitas Pahlawan Tuanku Tambusai, 2025)
Generally speaking, one of the most important factors in a company organization's success is staff management. Employee loyalty and persistence in a company are influenced by job satisfaction. Work satisfaction is strongly correlated with an individual's overall attitude toward his or her work, which is shaped by the company culture and work environment. The goal of this study is to determine how PPPPTK BOE Malang's organizational culture and work environment affect workers' job satisfaction. Using the Multiple Linear Regression Analysis Technique, the study methodology is descriptive quantitative. Saturated sampling is the method used for sampling in this study. 35 employees in all were selected as respondents out of the overall population. hypothesis utilizing the simultaneous test of F and the partial test of t. The results of the F test (simultaneous) indicate that organizational culture and work environment jointly influence employee PPPPTK BOE Malang's job satisfaction, while the results of the t test demonstrate that organizational culture and work environment have positive and significant effects on job satisfaction. Based on the findings, researchers recommended that the agency enhance organizational culture for PPPPTK BOE Malang's advancement, pay greater attention to comfort, and strengthen the regulations and discipline of the workplace for PPPPTK BOE Malang.